Delete that : (and other failed attempts to look good online) - Crist, John (Crown Forum, 2022)
"John Crist wasn't always recognizable as "the guy from that hilarious video in the grocery store." Growing up part of a homeschool family of ten in rural Georgia with Mennonite grandparents and a high-school job at Chick-fil-A, he was an unlikely candidate for Internet fame. Despite all that, or perhaps because of it, Crist passionately pursued his dream of stand-up comedy. In his first book, Crist offers heartfelt, laugh-out-loud observations on the absurd ways we all try to make ourselves look better online: like how we all post filtered pictures of our super healthy kale salads but somehow neglect to post about our 1 A.M. Uber Eats Big Mac. Or how quick we all are to post our "I Voted" sticker pictures but fail to post about the ways we vote with our dollars every day in ways that don't align with our loudly and publicly espoused values"--